Collapse failure analysis and fragility analysis of a transmission tower-line system subjected to the multidimensional ground motion of different input directions. (February 2023) - Tian, Li; Yang, Meng; Liu, Shiyuan; Liu, Juncai; Gao, Guodong; Yang, Zeying
Abstract: Transmission lines, which are important for maintaining economic and social operations, are vulnerable to collapse damage due to the effect of multidimensional ground motion. In this paper, a three-dimensional finite element model of a transmission tower-line system is established. Twenty ground motion records were selected from the international ground motion database. The acceleration time history is orthogonally decomposed to obtain the acceleration time history along the X direction and Y direction of the model in different input directions. Based on the incremental dynamic analysis method, the influence of different ground motion input directions regarding the collapse failure of transmission tower-line systems is studied. Taking the section draft ratio of the tangent tower as the criterion, the influence of the seismic input direction on the collapse of the peak ground acceleration (PGA) and vulnerable area of the tangent tower is analyzed. The influence of the input direction on the collapse fragility of transmission tower-line systems under different conditions is investigated based on the fragility analysis method, and the collapse margin ratio is used to evaluate the seismic capacity of transmission tower-line systems. A comparison of the results indicates that the input direction of the ground motion has a great influence on the collapse of the PGA, and the difference in the various directions is up to 0.34 g. Additionally, the change in the input direction makes it possible for collapse to occur between the fourth and fifth sections. Last, the results also indicate that the input direction of the ground motion has a great disturbance on the collapse fragility of transmission tower-line systems. The influence of the input direction of ground motion should be considered under the condition of rare ground motion (0.32–0.46 g) and extremely rare ground motion (0.54–0.64 g) in the design of the structure. The direction along and vertical to the tower-line is not the worst input direction of the transmission tower-line system. Considering only the seismic input of these two directions will cause a significant overestimation of the seismic capacities of transmission tower-line systems.